SÍNDROME COMPARTIMENTAL ABDOMINAL EN EL PACIENTE QUEMADO - Piccolo Johanning, Loretta (2011)
According to the World Society of Abdominal Compartment Syndrome(WSACS),the abdominal compartment syndrome is defined as "sustained intra-abdominal pressure > 20 mmHg (with or without abdominal perfusion pressure < 60 mmHg) associated with dysfunction or organ failure of recent onset "(1). It can affect different systems in the body, causing organ failure and eventually lead to death; therefore it is a diagnosis to be taken into consideration when assessing patients at risk. Surgical decompression of the abdominal cavity is the main treatment modality.